BK Nusantara's Approach in Multicultural Counseling: Reviving Traditional Values in the Modern Era - Fasha, Azba Novanda; Hidayah, Nur (Universitas Muria Kudus, 2024)
BK Nusantara's approach is an innovative response to the needs of multicultural counseling in Indonesia, which is rich in cultural diversity. This research highlights the importance of integrating traditional values such as mutual cooperation and deliberation in counseling practice. The results of the analysis show that this approach is effective in improving service acceptance, strengthening individual resilience, and creating a more contextual intervention model. Despite the challenges of synchronizing with modernity, this approach has great potential to become an inclusive and meaningful counseling paradigm. This study suggests strengthening the competence of multicultural counselors through adaptive training based on local wisdom.